Cork re-wall: computational methods of automatic generation and digital fabrication of cork partition walls for building renovation - Brandão, F. J.S.; Paio, A.; Sousa, J. P.; Rato, V. (Anais do XIX Congresso da Sociedade Ibero-americana de Gráfica Digital 2015, 2015)
Developments in computational design methods and their integration with digital fabrication processes are ushering a customized fabrication paradigm. This paradigm is particularly suited to renovation of old buildings built with traditional construction techniques, a diversified corpus in which interventions are surgical and unique, and where partition walls play the central role. Insulation Cork Board and OSB, natural and renewable materials, can have an important role in a material system that responds to this context. Cork re-Wall is a parametrically modeled construction system and a file-to-factory digital process to generate high quality custom solutions to respond to diverse renovation design challenges.